Study the Effect of Electrodeposition Parameters on Ni/SiC Composite Coating - Jaseem, Fatima N.; Jaleel, Mofeed A.L. (Al-Nahrain Journal for Engineering Sciences, 2017)
In this research, we successfully obtained Ni/SiC micro-composite coatings with various contents of SiC particles of particle size(10 ?m), by using electrodeposition method from nickel watts bath in which the SiC particles suspend. The effects of the current density, temperature, and particle loading(PL) of SiC particles in the electrolyte on the morphology, texture, and vol% of SiC in deposit were investigated. The morphological and structural analysis show uniform distribution of SiC particles within the composite coatings. It was found that the depositing conditions affect the microstructure of deposited nickel and the SiC vol% in deposit. Furthermore, the vol% of SiC increases in deposit by increasing the particle loading(PL) in the bath, while decreased by increasing the current density. Also the higher values of SiC vol% were obtained at temperature (50°C).